Thematic Features of Epigrams in English and Karakalpak Poetry (Texas Journal of Philology, Culture and History, 2026)
This article examines the differences between epigrams in English and Karakalpak poetry, with a concentration on the writings of A. Pope, W. Blake, and I. Yusupov. The study analyzes how epigrams may be used to communicate moral judgement, expose hypocrisy, and criticize social behavior by examining a few chosen examples. In all literary traditions, particular focus is placed on the intellectual depth, stylistic methods, and subject breadth of epigrams. Satire, moral and ethical reflection, social critique, and philosophical reflection are the four primary themes identified by the research. The results show that epigrams in English and Karakalpak literature serve similar purposes, such as satire, didacticism, and philosophical reflection, despite variations in historical and cultural context.